2014
DOI: 10.1016/j.ymeth.2014.02.023
|View full text |Cite
|
Sign up to set email alerts
|

Methods to study Drosophila immunity

Abstract: a b s t r a c tInnate immune mechanisms are well conserved throughout evolution, and many theoretical concepts, molecular pathways and gene networks are applicable to invertebrate model organisms as much as vertebrate ones. Drosophila immunity research benefits from an easily manipulated genome, a fantastic international resource of transgenic tools and over a quarter century of accumulated techniques and approaches to study innate immunity. Here we present a short collection of ways to challenge the fruit fly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
131
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(133 citation statements)
references
References 127 publications
2
131
0
Order By: Relevance
“…While a recent review of infection methods suggested that abdomen inoculation might be riskier due to imagined potential puncturing of the intestines, our data demonstrate that thorax inoculation is more detrimental (35). Drosophila immunity studies are somewhat divided between the two inoculation sites.…”
Section: Discussionmentioning
confidence: 57%
“…While a recent review of infection methods suggested that abdomen inoculation might be riskier due to imagined potential puncturing of the intestines, our data demonstrate that thorax inoculation is more detrimental (35). Drosophila immunity studies are somewhat divided between the two inoculation sites.…”
Section: Discussionmentioning
confidence: 57%
“…Brown, and YW) to the bacterial pathogens P. luminescens and E. faecalis and the nonpathogens E. coli and M. luteus. These bacteria are frequently used for understanding the insect immune system (23). Although the susceptibility of the five strains varied with the different types of infection, we consistently found that YW flies, and on one occasion w1118 flies, were particularly sensitive to all bacteria.…”
Section: Discussionmentioning
confidence: 65%
“…The voucher specimen was deposited at Biofarmaka Laboratory, Faculty of Pharmacy, Hasanuddin University. Fly infection and assays for survival and bacterial growth The introduction of bacteria into the thorax of male adult flies, known as pricking, was carried out according to the established procedures 33 with modifications. Briefly, at 4-7 days after eclosion, the flies (10 flies per vial, 3 vials in each experiment) were pricked with bacterial suspension containing given numbers of bacteria (1 × 10 5 cfu/ml) per fly.…”
Section: Sample Preparationmentioning
confidence: 99%
“…This indicates that Toll immunodeficient flies were more sensitive to bacterial infection, supporting the reports of previous investigators. 33,35 Furthermore, treatment of the infected-immunodeficient flies with food containing ethanolic extract of Ulva reticulata at concentration of 25 mg/ml increased the survivorship of infected Toll mutant flies and reduced the bacterial load recovered from the corresponding mutant flies ( Figure 4A). Similar results were also observed in Draper mutant flies lacking for cellular innate immunity ( Figure 4B).…”
mentioning
confidence: 96%